Estudos de dispersão de lagartas em milho e soja visando ao manejo de pragas no Brasil e EUA - Pannuti, Luiz Eduardo da Rocha [UNESP] (2015)
Corn (Zea mays L.) is one of the most cultivated crops worldwide. However, its productivity is constantly threatened by several factors such as the attack of insect pests. Among them stand out the species from Noctuidae family, including the fall armyworm Spodoptera frugiperda(J.E. Smith) (Lepidoptera: Noctuidae), the western bean cutworm Striacosta albicosta(Smith) (Lepidoptera: Noctuidae), and the old world cotton bollworm Helicoverpa armigera(Hubner) (Lepidoptera: Noctuidae). Alterations in crop systems such as off-season plantations and succession of host crops, combined with the extensive use of transgenic Bt corn, have been demanding more information related to various behavioral aspects of these insects, which can directly influence important components in the implementation of integrated pest management (IPM) and resistance management (IRM) of these pests. Some of these behavioral aspectsare not easy to observe in field conditions, and require the use of marking techniques for individuals. In this sense, this work aimed to evaluate the larval movement of noctuidae species in reproductive corn stages, as well as develop marking techniques for early instars and test their application in behavioral studies of these insects. Initially, the on-plant larval movement of the fall armyworm was investigated in field (US and Brazil), and greenhouse conditions (Brazil), as well as the feeding behavior of the larvae on different corn tissues in laboratory. In another study, the dispersion of the western bean cutworm and fall armyworm larvae was characterized in corn fields (USA). In the last step, new marking techniques of early larval instars were investigated forH. armigera, and their application were tested in a behavioral study at ...